A construção da expressividade na infografia: um estudo de criações de Jaime Serra - Pliger, Marcelo (2012)
The specific object of this study is the work of Spanish infographist Jaime Serra, recognized in his field for developing projects with expressive character. Our goal is to investigate how the communication of information is constructed in Serra s infographics. Infography is a diagrammatic combination of texts and images in many different fields of communication, including journalism. The research on this topic fits into the study of human communication manifestations and contributes to understand the current state of infographics and the critical discussion that seeks for guidelines for infographics creation process. We observed two groups: one that supports the development of objective, technical and scientific infographics and another that supports infographics with emphasis on subjectivity and aesthetic expressivity. Our main question is: how Serra articulates expression plane and content plane to build different layers of meaning? The theory base relates the graphic semiology developed by BERTIN (1967) and the graphic syntax theory by Yuri ENGELHARDT (2002). The first chapter presents significant historical moments that exploit the expressiveness in infographics, the presence of Serra s work in this context and the critical debate around the theme through the arguments of Edward Tufte, Alberto Cairo, and Nigel Holmes. In the second chapter we write about Bertin s visual variables theory and Engelhardt s graphic syntax theory. These two theories together with Greimas s semiotic provide the basis to study three examples of Serra s work in the third chapter. Through the observation of some common characteristics in infographics that explore new expression forms to communicate information, we concluded that the use of unusual instruments to create images in infographics - as the incorporation of elements of the cultural imaginary and the displacement of actors place in the enunciation - are resources that Serra uses in his creation process and that significantly participates in the construction of meaning communicated in his infographics